When environmental protection and human rights collide : the politics of conflict management by regional courts - Petersmann, Marie-Catherine (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
"This book will be of interest to students, scholars and practitioners interested in the protection of the environment and human rights. It questions the synergistic framing of the relationship between environmental protection and human rights by retrieving the numerous conflicts of norms that also underpin and define this relation"--
Introduction -- Narratives of environmental and human rights protection - from a 'pristine wilderness' to a 'human environment' -- Horizons of synergy - adjudicating environmental and human rights protection -- Constructing and contesting anthropocentric synergies -- Countering the dominant frame - an account of trade-offs and tensions -- The general interest as universalisation strategy -- Expert knowledge as universalisation strategy -- Conclusion.
Based on author's thesis (doctoral - European University Institute, 2019) issued under title: When environmental protection and human rights collide : studies in legal conflict and its management.
BIBINDX
Keywords: Environmental law, International; Human rights; International human rights courts